2015
DOI: 10.1111/pirs.12105
|View full text |Cite
|
Sign up to set email alerts
|

Are regional incomes in Malaysia converging?

Abstract: This paper analyses patterns in regional inequality within and between Malaysia's 14 states, drawing upon estimates of Kuznets/Williamson curves, σand β-convergence and spatial spillovers. The path of regional inequality contradicts Kuznets predictions. Regional inequality initially fell but has subsequently risen with further economic development. While Malaysian governments have been successful at reducing poverty, they have been unable to curtail regional inequality in the long run. JEL classification: O11,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Indeed, regional disparities have widened unabated in numerous contexts in spite of quite extensive government initiatives to curb imbalances (Abdullah et al 2015). As governments begin to make more substantive efforts to avert the mentioned adverse consequences that accrue to persistent poverty and spatial inequality, the challenge for the research community is to continue making progress in our understanding of why inequalities prove so resilient -even in the face of concerted policy action -and subscribe policies with pro-poor components and a necessary emphasis on closing urban-rural divides.…”
Section: Are Decentralised Territorial Approaches the Answer?mentioning
confidence: 99%
“…Indeed, regional disparities have widened unabated in numerous contexts in spite of quite extensive government initiatives to curb imbalances (Abdullah et al 2015). As governments begin to make more substantive efforts to avert the mentioned adverse consequences that accrue to persistent poverty and spatial inequality, the challenge for the research community is to continue making progress in our understanding of why inequalities prove so resilient -even in the face of concerted policy action -and subscribe policies with pro-poor components and a necessary emphasis on closing urban-rural divides.…”
Section: Are Decentralised Territorial Approaches the Answer?mentioning
confidence: 99%
“…Another important reported ingredient of income inequality reduction is education. Such finding is a rejoinder to the findings of Barro (2000), De Gregorio and Lee (2000), Odedokun and Round (2004), and a metaanalysis from Abdullah et al (2015) also found that educational attainment leads economies toward more equal income distribution. Government expenditure is reported to have a negative relationship with income inequality, probably because of its redistributive role in the economy and terms of investment.…”
Section: Analysis and Discussionmentioning
confidence: 67%
“…Assessments of the degree of theconsequence of overqualification and overskillingbetween large and small labour marketmay seemdecisive for policymakers as such incidences are typically ending up in negative rather than positive outcomeseither at an individual nor at a firm level. 1 The negative outcome at both levels may drive down local economic performance and leads to an unequal distribution of economic development between smaller and larger region. Thismay seem to be truly in the context of Malaysia as differences in educational attainment, unemployment, occupationor education and skills utilisationhas led to regional income inequalities and unbalanced growth among states (Yussof & Kasim, 2003;Ragayah, 2008 Nevertheless, if the supply of highly educated workers is not in line by demand at the state labour market level, then the impact of education and skill on state Growth Domestic Product (GDP) may not as high as expected relative to if the state werefully utilised the education and skills of all the mismatched workers(McGowan and Andrews, 2017; Adrian, Desislava, Ganev, & Aleksiev, 2018).…”
Section: Introductionmentioning
confidence: 99%